Highly variable mutational profile of ASXL1 in myelofibrosis. (19th January 2016) - Sorigué, Marc; Ribera, Josep‐Maria; García, Olga; Cabezón, Marta; Vélez, Patricia; Marcé, Silvia; Xicoy, Blanca; Fernández, Cristalina; Buch, Joan; Cortes, Montserrat; Plensa, Esther; Gallardo, David; et al.
Abstract: Objective: Somatic mutations in ASXL1 seem to have a negative prognostic impact in patients with several myeloid neoplasms, including myelofibrosis (MF). The aim of this work was to determine the prevalence and profile of ASXL1 mutations in MF. Methods: We analyzed mutations in ASXL1 in 70 consecutive MF patients from 8 Spanish hospitals by means of Sanger sequencing, as well as JAK2, CALR, and MPL mutations. Results: ASXL1 mutations were found in 16/70 (23%) of cases, most commonly p.Gly646TrpfsX12 (5/16). Most mutations (13/16) were frameshift mutations. Of 54 ASXL1 ‐ wild‐type patients, 32 (59%) had at least one single nucleotide polymorphism (SNP), 27 of them had g.78128C>T, g.79017A>C, and g.79085T>C [triple SNP (TSNP) patients]. The 5‐yr overall survival probability of TSNP patients was 67% (95% CI, 43–91%) vs. 90% (95% CI, 77–100%) in ASXL1 ‐WT patients ( P = 0.152). Conclusion: ASXL1 mutations were found in 23% of cases, p.Gly646TrpfsX12 being the most frequent. About 85% of mutations were found only in individual cases and 46% had not previously been reported, a pattern also seen in other series. Fifty percent of ASXL1 ‐WT patients had a combination of three specific SNPs that might have a prognostic correlation that needs to be determined in larger series.